An electrodeless atmospheric microwave plasma jet for efficient degradation of antibiotic norfloxacin. (1st August 2021) - Xue, Li; Zhao, Chaoxia; Mo, Qi; Zhou, Yanping; Huang, Kama
Abstract: Plasma technology is increasingly being used for the degradation of residual antibiotics in aquatic environments. However, the electrodes in conventional plasma generators are subject to erosion, which can pollute the reaction system and shorten its lifetime. To overcome these drawbacks, we developed an electrodeless high-flow atmospheric microwave plasma jet (MPJ) for fast and efficient degradation of residual norfloxacin (NOR), a typical fluoroquinolone antibiotic that is frequently detected in the aquatic environment owing to its widespread use in the treatment of various infectious diseases. Stable plasma was generated through a low-cost magnetron with the assistance of injection-locking technology. The degradation efficiency of NOR (20 mg/L) reached 98.27 ± 1.03% at 6 min and the mineralisation efficiency reached 68.67 ± 3.21% at 15 min. The fast degradation process of the NOR solution contributes to the large cross-section (approximately 153 mm 2 ) of the plasma in direct contact with the solution. Hydroxyl radical ( OH) scavengers were used to identify the generated oxidising species, which indicated that their non-selective oxidation plays a major role in NOR degradation. Three main possible degradation pathways and mechanisms were proposed, namely the attack of OH on the piperazine ring, quinolone ring, and benzene ring. The NOR solution was not toxic to Escherichia coli after 20 min of degradation. Thus, the high-flow atmospheric MPJ is an effective technology for the degradation of antibiotics in aqueous solutions. Graphical abstract: Image 1 Highlights: An electrodeless high-flow atmospheric microwave plasma jet for fast degradation of NOR. Injection locking technology helps low-cost magnetrons to produce stable plasma. The antimicrobial activity of treated NOR against E. coli was completely eliminated. Three possible degradation pathways were proposed.